Activating more students through blended online and in-class discussions - Skovmand Bosselmann, Aske (Improving University Science Teaching and Learning, 2023)
This study shows that teachers in international classes can use blended online and in-class discussions to activate more students from a student group with diverse educational cultures and different preferences for mode of discussion, thereby contributing to improved learning via several mechanisms, than any one mode of discussion can do alone. This has implications for the use of discussions in courses, where blended teaching is possible.